1989
DOI: 10.1007/bf01995860
|View full text |Cite
|
Sign up to set email alerts
|

Familial combination of brachydactyly, type E and atrial septal defect, type II

Abstract: Nine members of a three generation family were affected with the combination of brachydactyly, type E and heart defect, mainly atrial septal defect, type II. A similar malformation pattern of autosomal dominant origin has not previously been delineated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Therefore, the similar frequencies between men and women documented in this study may be more representative of the actual sex distribution of the Type II accessory navicular because it eliminates the presentation bias inherent in clinical settings. The findings of the present study are also consistent with the numerous pedigrees that have established an autosomal dominant inheritance pattern for this trait (Wildervanck et al ., 1967; Czeizel & Goblyos, 1989; Kiter et al ., 2000; Dobbs & Walton, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the similar frequencies between men and women documented in this study may be more representative of the actual sex distribution of the Type II accessory navicular because it eliminates the presentation bias inherent in clinical settings. The findings of the present study are also consistent with the numerous pedigrees that have established an autosomal dominant inheritance pattern for this trait (Wildervanck et al ., 1967; Czeizel & Goblyos, 1989; Kiter et al ., 2000; Dobbs & Walton, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Several family pedigrees have been established over the last three decades in an effort to document the inheritance pattern of the accessory navicular (Table 1), which McKusick (1966) first asserted as being autosomal dominant in his book on Mendelian inheritance. Although McKusick did not present any data to buttress his claim, recent studies seem to confirm that the accessory bone does, indeed, represent an autosomal dominant trait with incomplete penetrance (Wildervanck et al ., 1967; Czeizel & Goblyos, 1989; Kiter et al ., 2000; Dobbs & Walton, 2004). Kiter et al .…”
Section: Heritabilitymentioning
confidence: 99%
“…[ 42 ] concluded that 'brachydactyly E is indistinguishable radiologically from the PHP-PPHP syndrome'. Short stature, round facies, secundum type of atrial septal defect and BDE (in which shortening of the metacarpals was most pronounced but not limited to the 4th metacarpal), were described in a kindred by Czeizel and Göblyös [ 43 ].…”
Section: Types Of Isolated Brachydactylymentioning
confidence: 99%
“…Vice versa, patients with ASD, particularly when a hereditary character exists, should be examined for musculoskeletal defects of their limbs [9]. Macroscopic examination frequently needs to be validated radiologically [13,14]. Genetic control is not mandatory in all heart-limb syndromes, if the phenotype is unequivocal [3].…”
mentioning
confidence: 98%